2013
DOI: 10.1073/pnas.1302428110
|View full text |Cite
|
Sign up to set email alerts
|

Climbing, falling, and jamming during ant locomotion in confined environments

Abstract: Locomotion emerges from effective interactions of an individual with its environment. Principles of biological terrestrial locomotion have been discovered on unconfined vertical and horizontal substrates. However, a diversity of organisms construct, inhabit, and move within confined spaces. Such animals are faced with locomotor challenges including limited limb range of motion, crowding, and visual sensory deprivation. Little is known about how these organisms accomplish their locomotor tasks, and such environ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…From measurements of the cross-sectional area of fire ant foraging tunnels 59 , we estimate the effective diameter of horizontal foraging tunnels in nature to be, D = 7.8 ± 1.9 mm (tunnels are elliptical in cross-section with eccentricity of 2, See 35 ). Vertical nest entrance tunnels in natural nests were reported in the range of 3-4 mm in diameter and a laboratory x-ray study found that vertical tunnels were D = 3.7 ± 0.8, See 60 . ∆τ * is a diverging function with decreasing diameter and predicts that bi-directional traffic should be impossible in tunnels smaller than D c = 1.47 mm.…”
Section: Effects Of Tunnel Diametermentioning
confidence: 99%
“…From measurements of the cross-sectional area of fire ant foraging tunnels 59 , we estimate the effective diameter of horizontal foraging tunnels in nature to be, D = 7.8 ± 1.9 mm (tunnels are elliptical in cross-section with eccentricity of 2, See 35 ). Vertical nest entrance tunnels in natural nests were reported in the range of 3-4 mm in diameter and a laboratory x-ray study found that vertical tunnels were D = 3.7 ± 0.8, See 60 . ∆τ * is a diverging function with decreasing diameter and predicts that bi-directional traffic should be impossible in tunnels smaller than D c = 1.47 mm.…”
Section: Effects Of Tunnel Diametermentioning
confidence: 99%
“…The study of climbing has led to undiscovered templates (11) that define physical interactions through frictional van der Waals adhesion (12,13) and interlocking with claws (14) and spines (5). Burrowing (15,16), sand swimming (17), and locomotion in tunnels (18) have yielded new findings determining the interaction of bodies, appendages, and substrata.…”
mentioning
confidence: 99%
“…Locomotion in confined environments offers several challenges for animals (18) that include limitations due to body shape changes (19,20), restricted limb mobility (21), increased body drag, and reduced thrust development (22). Examining the motion repertoire of soft-bodied animals (23), such as annelids (19), insect larvae (24), and molluscs (25), has offered insight into a range of strategies used to move in confined spaces.…”
mentioning
confidence: 99%
“…As we are unable to distinguish antennae from legs, and antennae do not contribute to the tensile integrity of the structure, they are excluded from our analysis (see Materials and methods, 'Calculation of measurements'). However, while antennae have no role in supporting tensile forces, they may be important in providing resistance to compressive stresses, as shown by the ability of ants to arrest falling in tunnels by extending their antennae (Gravish et al, 2013).…”
Section: Reproducibility Of Ct Scansmentioning
confidence: 99%